2010
DOI: 10.1111/j.1574-6976.2010.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of gene expression inCorynebacterium glutamicum: the role of global, master and local regulators in the modular and hierarchical gene regulatory network

Abstract: The genus Corynebacterium belongs to the taxonomic class Actinobacteria representing the high G+C branch of gram-positive bacteria. Among the most prominent members of this genus is Corynebacterium glutamicum, which is used by the biotechnological industry for the fermentative production of l-amino acids. Because of its industrial importance, C. glutamicum is one of the best-studied gram-positive bacteria and an emerging model for the suborder Corynebacterineae. Over the past years, the transcriptional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 272 publications
(929 reference statements)
5
88
0
Order By: Relevance
“…The current study demonstrated a new regulatory connection between GlxR and RamA, which has a great impact on the C. glutamicum genome-wide transcriptional regulatory network structure (56), because the connection not only expands the GlxR regulon by including the RamA regulon but also newly creates multiple feed-forward loops (FFLs) in the regulatory cascades. The FFL, which is one of the most significant network motifs found in a transcriptional regulatory network in both E. coli (57) and Saccharomyces cerevisiae (58), comprises two cascaded transcription factors that jointly regulate a common gene (59).…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated a new regulatory connection between GlxR and RamA, which has a great impact on the C. glutamicum genome-wide transcriptional regulatory network structure (56), because the connection not only expands the GlxR regulon by including the RamA regulon but also newly creates multiple feed-forward loops (FFLs) in the regulatory cascades. The FFL, which is one of the most significant network motifs found in a transcriptional regulatory network in both E. coli (57) and Saccharomyces cerevisiae (58), comprises two cascaded transcription factors that jointly regulate a common gene (59).…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable to suggest that intermediates of maltose metabolization trigger the positive effect on ptsG expression. In C. glutamicum, transcription of ptsG is controlled by the global regulators RamA, RamB, GlxR, and SugR (27,57,65), which all coordinate the adaptation of the central metabolism of C. glutamicum toward the utilization of carbon sources requiring gluconeogenesis, such as acetate (54). Repression of ptsG in the presence of acetate is mainly caused by SugR (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in metabolic engineering of C. glutamicum open up new possibilities for efficient utilization of substrates containing mixtures of D-glucose, D-xylose, and L-arabinose (9)(10)(11)(12). Understanding of the unique transcriptional regulatory system of sugar metabolism genes in C. glutamicum (13,14) highlights a potential avenue toward optimization of utilization of sugar mixtures derived from a variety of lignocellulosic feedstocks.…”
mentioning
confidence: 99%